Perspektif Jemaat tentang Mempersembahkan Tubuh sebagai Ibadah yang sejati Berdasarkan Roma 12:1-2 di Kehidupan keluarga Kristen GKPPD Prongil Jehe - Jipora Ngotmaina Cibro; Bernhardt Siburian; Megawati Manullang; Junjungan Simorangkir (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
This research aims to determine the perspective of the congregation offering the body in the life of the GKPPD Prongil Jehe Christian family. This study uses a qualitative method. The technique for determining informants is Purposive Sampling based on certain criteria that are appropriate to the research topic. The number of participants who will be interviewed is 10 people. The data collection technique for this research is to use observations on 3-5 October 2023 and documentation in the form of pictures. The results of research conducted by the author on the GKPPD Prongil Jehe congregation have provided an understanding of offering the body to continue to strengthen relationships with others and with God. There are two factors that influence the congregation regarding offering the body, namely internal factors, need factors and interest factors where there is a sense of joy and desire that arises without any external encouragement. The second is external factors, factors that come from outside the congregation, namely the leadership of the pastor, the service of the servants, the church infrastructure (facilities). These two factors influence the congregation's perspective regarding offering the body as true worship in the life of the GKPPD Prongil Jehe Christian family.